TECHNOLOGIES FOR TESTING RELATIVE INDICATORS OF PHYSICAL FITNESS OF DISABLED PEOPLE IN THE FORMAT OF THE VFSK GTO - Aksenov, A.V.; Ladygina, E.B.; Kryukov, I.G.; Grachikov, A.A. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to test the technology of using (testing) the relative indicators of physical fitness of disabled people within the framework of the All-Russian physical culture and sports complex "Ready for Labor and Defense" (GTO) for disabled people. Methods and structure of the study. To achieve this goal, within the framework of the state assignment for research work on the topic “Research of means and methods aimed at forming motivation, in persons with disabilities (taking into account sensory, motor and mental disorders) for systematic physical culture and sports on the example of the All-Russian physical culture and sports complex "Ready for Labor and Defense" (VFSK GTO) for the disabled (2020-2022) "based on the order of the Ministry of Sports of Russia No. 1034 dated December 14, 2018, in accordance with the terms of reference, the working group analyzed the results of the participation of people with disabilities with hearing, vision, musculoskeletal and intellectual disabilities in the VFSK GTO for the disabled. We studied individual protocols for testing the physical fitness of people with disabilities, various nosological groups, both primary and the results of re-applying to testing centers in order to improve their result or receive a distinction for the next age group, for the period 2019-2021. Results and conclusions. In the process of conducting research, positive dynamics was revealed in the indicators of physical fitness of disabled people of various nosological groups, expressed in improving the results of repeated fulfillment by participants of the test standards (tests) of the VFSK GTO for disabled people, which confirms the need to introduce relative indicators that reflect the individual dynamics of indicators of physical fitness of the contingent with disabilities.